2020
DOI: 10.1002/cae.22307
|View full text |Cite
|
Sign up to set email alerts
|

Using process simulators in Chemical Engineering education: Is it possible to minimize the “black box” effect?

Abstract: Simulators are instrumental to engineers and scientists, in general, and to chemical engineers,more specifically, which enable the optimization and analysis of alternative solutions in a time‐efficient and cost‐effective way. Thus, their integration into Chemical Engineering studies has gained traction over the years in supporting traditional lectures or as the sole tool for knowledge transmission. However, despite their proven benefits in Higher Education, limitations exist, as the application of the tool may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The value and challenges of such approaches, have been broadly reported in clinical education literature (Croft et al, 2019;Sarfati et al, 2019;Ferguson et al, 2020). However, the use of in silico, or computer-based process simulations tends to be reported more in educational literature relating to physical sciences, for example, chemical engineering (Li & Huang, 2017;Rasteiro & Urbano, 2017;de Lucas-Consuegra, Serrano, & Llanos, 2018;Golman & Yermukhambetova, 2019;Moodley, 2020;Nachtigalova et al, 2020;Roman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value and challenges of such approaches, have been broadly reported in clinical education literature (Croft et al, 2019;Sarfati et al, 2019;Ferguson et al, 2020). However, the use of in silico, or computer-based process simulations tends to be reported more in educational literature relating to physical sciences, for example, chemical engineering (Li & Huang, 2017;Rasteiro & Urbano, 2017;de Lucas-Consuegra, Serrano, & Llanos, 2018;Golman & Yermukhambetova, 2019;Moodley, 2020;Nachtigalova et al, 2020;Roman et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While not engaging in programming the code, this insight can be considered valuable to the user in terms of understanding the fundamentals of an in-silico simulation approach. The need to engage students with the simulation code/basic equations and therefore the fundamental principles underpinning the process simulation, in order to mitigate concerns relating to superficial learning using process simulation tools, has been recognised (Roman et al, 2020).…”
Section: Covid-19 Special Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation of distillation columns by an equilibrium model was first studied in 1899 by Sorel for steady-state systems [1][2][3]. In 1922, Ponchon and Savarit modified the equilibrium equations by involving the interactions between components in binary systems [4,5]. In 1925, Murphree showed that the concept of equilibrium trays could not simply be used to accurately predict the separation patterns of the distillation column in more complex multicomponent systems [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The School of Engineering at the University of Huelva, thanks to various Teaching Innovation Projects, is currently implementing the use of Mathcad in some courses corresponding to a Bachelor's Degree in Industrial Chemical Engineering and a Master's Degree in Chemical Engineering [5,6,21,22]. As for the CRE area, we used Mathcad for the design of isothermal reactors involving multiple reactions (series and parallel reactions) [6].…”
Section: Introductionmentioning
confidence: 99%